Development of viroid free nucleus material for rootstock of citrus: an approach for management of yellow corky vein disease - PADMA RAMACHANDRAN*, ANIRBAN ROY and (Indian Phytopathology, 2008)
Yellow corky vein disease of citrus has been shown to be associated with two viroids,citrus exocortis viroid (CEVd) and hop stunt viroid (HSVd). The disease causes heavy yield reduction: Viroid-free nucleus material for rootstocks (rough lemon and trifoliate orange) have been developed after’ standardization of micropropagation protocol. Present study constitutes the first record of development of viroid-free rootstock plant for citrus through micropropagation. Growth pattern of two species are slightly different; initial shooting is higher in trifoliate orange, but callusing and rooting are much faster in rough lemon. Viroid free micropropagated plants were indexed by NASH test using radiolabelled cDNA probes to two groups of viroid viz. citrus exocortis viroid and hop stunt viroid.